Public preferences for livestock presence in pasture landscape: A latent class analysis of a discrete choice experiment in Germany - Henning Schaak; Oliver Mußhoff (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2019)
Biodiversity, landscape aesthetics and grazing livestock have significant relevance for agricultural production, however they are rarely considered in public landscape preferences research. This paper studies public preferences for pasture usage by the means of a discrete choice experiment using a sample of 449 individuals from Germany. Graphical representations of the choice sets are used to assess the preferences for the presence of livestock and typical pasture landscape elements. To account for preference heterogeneity, the paper utilises a latent-class logit model. Four different latent classes can be identified. The results show different preferences between the latent classes, not only in terms of the magnitude of the estimated parameters, but also in terms of the parameter signs. This indicates that there are multiple types of preferred pasture landscapes. Furthermore, the paper discusses the influence of sociodemographic variables on the class membership probabilities and presents the calculated willingness to pay for the landscape attributes and the livestock visibility.
Keywords: 330